(untitled) (PYC Nepal Journal of Management, 2017)
This study assesses the impact of remittance on Gross Domestic Product (GDP), Gross National Product (GNP) and Per Capita Income (PCI) of Nepal employing multiple regression method on national annual time series data for a period of 41 years (from 1974/75 to 2014/15). The results show that there is positive impact of remittance on GDP, GNP and PCI. Further, the findings clearly provide an evidence of predictive power of fixed capital formation on economic development. But the role of export could not be established. Finally, to foster the economic development, it is suggested that the government should initiate policy to channelize the remittance income into the productive uses by offering attractive investment schemes to the remittance receiving families.